2020
DOI: 10.3390/cancers12082314
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Adverse Events of Nivolumab in Non-Small Cell Lung Cancer Patients—Literature Review

Abstract: In recent years, we have observed significant progress in cancer treatment associated with the development of immunotherapy. A programmed cell death 1 molecule (PD-1) on the surface of T lymphocytes may be stimulated via a specific PD-ligand 1 (PD-L1), which inhibits lymphocyte activation and leads to apoptosis. Some malignant cells are characterized by high PD-L1 expression. Nivolumab, an anti-PD-1 antibody, blocks the interaction between PD-1 and its ligands and inhibits the signaling pathway by preventing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 96 publications
0
8
0
Order By: Relevance
“…Chen ( Chen et al, 2014 ), have found that 0–20% of NSCLC is associated with NED and inhibition of the Akt signaling pathway. Clinical manifestations, natural course, pathological changes, and treatment response are all characteristic of NED and have become a new field of lung cancer research ( Dudzińska et al, 2020 ). Ma et al ( Ma and Zhang, 2015 ), in 2015, found that with a positive rate of 72.3%, the expression of Rap1b was significantly higher in NSCLC tissues compared to that in paraneoplastic tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Chen ( Chen et al, 2014 ), have found that 0–20% of NSCLC is associated with NED and inhibition of the Akt signaling pathway. Clinical manifestations, natural course, pathological changes, and treatment response are all characteristic of NED and have become a new field of lung cancer research ( Dudzińska et al, 2020 ). Ma et al ( Ma and Zhang, 2015 ), in 2015, found that with a positive rate of 72.3%, the expression of Rap1b was significantly higher in NSCLC tissues compared to that in paraneoplastic tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Only one patient with pituitary gland inflammation required systemic steroid therapy. Management of irAE’s includes the use of prednisone or the equivalent in anti-inflammatory doses (0.5–2 mg/kg) from Grade 2 for pituitary inflammation and in Grade 3–4 for adrenal insufficiency [ 5 , 9 , 63 65 ]. Recommendations regarding thyroid dysfunction include levothyroxine treatment for persistent hypothyroidism and symptomatic treatment for hyperthyroidism/thyrotoxicosis, usually without the need for immunosuppression and without the need to modify the dose of nivolumab [ 5 , 9 , 63 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Management of irAE’s includes the use of prednisone or the equivalent in anti-inflammatory doses (0.5–2 mg/kg) from Grade 2 for pituitary inflammation and in Grade 3–4 for adrenal insufficiency [ 5 , 9 , 63 65 ]. Recommendations regarding thyroid dysfunction include levothyroxine treatment for persistent hypothyroidism and symptomatic treatment for hyperthyroidism/thyrotoxicosis, usually without the need for immunosuppression and without the need to modify the dose of nivolumab [ 5 , 9 , 63 65 ]. Destructive thyroiditis with a phase of transient hyperthyroidism, which is estimated in the literature at 3.2–6.5% [ 15 ], often quickly passes in the hypothyroid phase, observed up to 16 to 32 days after the last documented TSH suppression [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Keynote-001 ( 26 ), 21% of patients receiving pembrolizumab for the management of NSCLC experienced thyroid dysfunction requiring eventual supplementation. Subsequent clinical experience with immunotherapy of NSCLC has confirmed an estimated incidence of endocrine irAEs of less than 23% with the overwhelming majority involving the thyroid and rarely exceeding grade 2 ( 27 , 28 ). Hypophysitis secondary to anti-PD-1/PD-L1 therapy is considered extremely rare and more frequently observed secondary to anti-CTLA-4 therapy ( 29 31 ).…”
Section: Discussionmentioning
confidence: 99%